Correlation Between Quantum Confinement Effect and Characteristics of Thin-Film Transistors in Solution-Processed Oxide-Based Thin-Films - Jinyeong Lee; Jaewook Jeong (IEEE Journal of the Electron Devices Society)
In this paper, the photoluminescence characteristics of solution-processed amorphous ZnO and related compounds of InZnO and GaZnO thin films were comparatively analyzed. Depending on the molarity of the precursor solution, PL emission peaks ranging from 382.4 nm to 384.8 nm were observed for the ZnO thin films. The PL emission peaks were closely related to the surface morphology of the thin films, which were clearly observed when isolated, nano-sized particles of quantum dot structure were present, leading to quantum confinement effect in the ZnO and GaZnO thin films. When uniform thin films formed, the PL emission peaks disappeared due to the increase of electrical and morphological connectivity, which reveals that the analysis of PL emission peak can be used to evaluate the film quality and the performance of thin-film transistors (TFTs) in solution-processed oxide-based materials.